2017
DOI: 10.1371/journal.pone.0182055
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and metabolite profiling of gibberellin biosynthesis during induction of somatic embryogenesis in Medicago truncatula Gaertn

Abstract: Gibberellins (GAs) are involved in the regulation of numerous developmental processes in plants including zygotic embryogenesis, but their biosynthesis and role during somatic embryogenesis (SE) is mostly unknown. In this study we show that during three week- long induction phase, when cells of leaf explants from non-embryogenic genotype (M9) and embryogenic variant (M9-10a) were forming the callus, all the bioactive gibberellins from non-13-hydroxylation (GA4, GA7) and 13-hydroxylation (GA1, GA5, GA3, GA6) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 108 publications
1
32
0
Order By: Relevance
“…The GA biosynthesis pathway involves many genes besides CPS ( Figure 5 B). According to the reference [ 54 ], we tested the expression level of the putative genes ( Table S2 ) in the GA biosynthesis pathway of M. truncatula stem tissue. The results showed that most GA biosynthesis genes were highly upregulated in the mnp1-1 mutant, while a small proportion of the genes ( MtKS , MtKAO1 , MtCYP714_A1 , MtCYP714_C2 ) showed a low level of upregulation, with no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…The GA biosynthesis pathway involves many genes besides CPS ( Figure 5 B). According to the reference [ 54 ], we tested the expression level of the putative genes ( Table S2 ) in the GA biosynthesis pathway of M. truncatula stem tissue. The results showed that most GA biosynthesis genes were highly upregulated in the mnp1-1 mutant, while a small proportion of the genes ( MtKS , MtKAO1 , MtCYP714_A1 , MtCYP714_C2 ) showed a low level of upregulation, with no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic tree was constructed using the Maximum-Likelihood method in MEGA7 41 , with bootstrap analysis of 1,000 replicates for stability testing of the tree nodes. Identification of other GA biosynthesis pathway genes, including CPS , KS , KO , KAO , GA13OX , and GA3ox , in the M. truncatula genome (Mt4.0) was also performed by BLASTP search (E value cutoff of E −10 and query coverage of 50%) using the previously reported GA biosynthesis genes of M. truncatula 42 as the seed queries.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Jiménez and Bangerth ( 2000 , 2001a , b ) and Jiménez et al ( 2005 ) found no difference between GAs levels in cultures of grapevine, carrot, and wheat showing different embryogenic characteristics. Previously, we showed that during a 3-week induction phase in Medicago truncatula, when the cells of the leaf explant from embryogenic (M9-10a) and non-embryogenic (M9) genotypes dedifferentiate to form callus, all the active gibberellins from 13-hydroxylation pathway (GA 1 , GA 3 , GA 6 ) as well as from the non-13-hydroxylation pathway (GA 4 , GA 7 ) are present (Igielski and Kępczyńska 2017 ). However, the contents of GA 3 and also of GA 6 were observed to increase in the M9-10a genotype as the induction phase progressed.…”
Section: Introductionmentioning
confidence: 99%